The Book of Genes and Genomes - Haga, Susanne B. (New York, NY : Springer New York : Imprint: Springer, 2022)
The Book of Genes & Genomes presents a concise overview of the advances in genetics and genomics and provide the unfamiliar reader with a succinct description of many of the applications and implications of this field. Given the substantial investment in genetics and genomics over the past several decades and the many recent discoveries and developments, this book will help the reader begin to understand the importance of genetics and genomics to us all. This exciting new title includes information on how genetics and genomics has advanced our understanding of health and medicine, evolution, and biology, as well as how they are pushing the boundaries of ethics and social values. Assumes no prior knowledge on the part of the reader; Easy to understand writing style, enabling novices to read and speak the "language" of genes and genomes; Inclusion of case-studies that depict how genes and genomics have advanced understanding of health, medicine, evolution and biology, but juxtaposed to ethics and social values; Recommended reading offered to facilitate self study; Clear, up to date and affordable.
Keywords: Genetics; Medical genetics; Genomics; Genetics; Medical Genetics; Genomics; Genetics and Genomics